2013
DOI: 10.1021/jf304970g
|View full text |Cite
|
Sign up to set email alerts
|

Application of Box-Behnken Experimental Design to Optimize the Extraction of Insecticidal Cry1Ac from Soil

Abstract: A validated method for analyzing Cry proteins is a premise to study the fate and ecological effects of contaminants associated with genetically engineered Bacillus thuringiensis crops. The current study has optimized the extraction method to analyze Cry1Ac protein in soil using a response surface methodology with a three-level-three-factor Box-Behnken experimental design (BBD). The optimum extraction conditions were at 21°C and 630 rpm for 2 h. Regression analysis showed a good fit of the experimental data to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Although toxicity was detected, the LC 50 was 3 orders of magnitudes higher than concentration of Cry1Ac protein found in soil from cotton fields where Bt transgenic cottons had been cultivated for several years (0.94 ± 0.08 ng/g dw). 27 In addition to sediment bioassays, water-only toxicity testing was also conducted. Different from the sediment toxicity testing, CK exhibited slightly higher toxicity to both organisms in water than that of NC and SC, but they were still less than 20% (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although toxicity was detected, the LC 50 was 3 orders of magnitudes higher than concentration of Cry1Ac protein found in soil from cotton fields where Bt transgenic cottons had been cultivated for several years (0.94 ± 0.08 ng/g dw). 27 In addition to sediment bioassays, water-only toxicity testing was also conducted. Different from the sediment toxicity testing, CK exhibited slightly higher toxicity to both organisms in water than that of NC and SC, but they were still less than 20% (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27 Briefly, after adding 1.2 mL PBST/SDS extraction solution, the soil or sediment sample was vortexed for 30 s, and the extraction was conducted at 21°C…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first study aiming to optimize the conditions of steam disinfection using the BBD. The BBD has been previously applied to optimize the removal efficiency of some heavy metals or residual chemical compounds in contaminated soil [ 38 , 39 , 40 ]. The findings of our study can be used as basic data for improving the disinfection efficiency and cost-effectiveness of high-temperature steam disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a literature survey showed that different types of experimental design were used for the investigation of Co sorption by potential sorbent materials such as apatite, zeolite, bauxite residue, and dried activated sludge [23][24][25]; however, DOE approach has not been applied, to this point, for the study of Co sorption or leaching from the soil matrix. In fact, just a few examples of RSM application for the analysis of a soil remediation process can be found [26,27]. In this study, a three-level-three-factor Box-Behnken experimental design was selected for the evaluation of the effect of factors which influence the Co extraction from contaminated soil.…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%